KEPRIBADIAN DAN MEMORI - Esti Hayu Purnamaningsih (Buletin Psikologi, 2008)
The effects of personality variable on memory has never been mentioned in almost all books of cognitive psychology. This short paper reviews some studies that found the effects of neuroticism, extraversion, anxiety or emotional instability on the ability to recall information.